Empirical methods for bioethics a primer - Jacoby, Liva; Siminoff, Laura A. (Elsevier JAI, 2008)
In recent years concerns over the use of results of scientific advances, expectations about how medical decisions are made, and demographic changes have raised ethical questions about how resources are allocated, and how the principles of beneficence, and respect for patient autonomy are applied. The effect that bioethics can have on policy decisions and health care delivery demand an enhanced approach to our understanding of such complex issues. This volume opens a window to how empirical social research can be used to illuminate and answer such quandaries and offers a practical resource for those wishing to engage in this type of research. Through a thorough look at both quantitative and qualitative methods utilized in key research investigations in bioethics, the book examines the impact of such investigations on clinical and policy decision-making, scholarship and on the advancement of theory.The varied sociological and anthropological research examples that are presented allow readers to better understand the richness and breadth of such work as well as relevant practical and theoretical approaches. Last, but not least, the book aims to stimulate further discussion of avenues toward a more solid integration of bioethics and empirical social research and, in that process, further our understanding of the complex bioethical environment surrounding us. This book offers insights into clinical and policy implications of empirical research, enhances understanding of methodologies as applied to bioethics. It is comprehensive - gives a range of examples of empirical bioethics studies, interdisciplinary - geared to a wide audience and a reference source - includes a large number of references.
Keywords: Life sciences -- Research -- Methodology.; Bioethics.; Bio-ethics.; Science -- Research & Methodology.; elektronické knihy; electronic books